Sistemas logísticos : estudos de caso em três cadeias de suprimentos no segmento de motores para automóveis - Bonadio, Patricia Viera Grizola (2008)
The worldwide (and thus Brazilian) automotive industry has undergone a process of important changes. Specifically in Brazil, the set up of new automakers, the consolidation and denationalization of the auto parts, and phenomena like the lowdisplacement engines have brought major strategic implicates to those companies, as well as to the supply chain to which they belong. Considering such implications, it is plausible to accept that several organizational elements were strongly impacted, including Supply Chain Management and Logistics. In this sense, the work has the prime objective to identify and analyze the logistics of three car-engine assemblers and some of their first and second- tier suppliers, discussing the relations between the logistics of each assembler and its suppliers in each supply chain studied. The hypothesis was formulated through literature review on the issues concerning this theme was carried out, as wells as a field research. Such research comprised case studies in three chains, led by assemblers with distinct strategies, with different levels of vertical interaction, representing distinct configurations. The case studies were conducted in the three assemblers and some of their suppliers (from the first and second tiers, in each chain), base don semi-structured interviews. The results indicate that, in general, the chain in function the structure and relations with supply implement logistics systems different.